The Principle of Personality of Tax Penalties: A General Principle with a Narrow Scope? - Gutmann, Daniel (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
The principle of personality of tax penalties is well established in the case law of the European Court of Human Rights. It is also very important in the case law of the French administrative Supreme Court. However, this principle may conflict with traditional institutions of tax law such as, for example, joint taxation of couples or group tax consolidation. This article studies the technical consequences of the principle of personality of tax penalties in a variety of tax matters and describes how the French case law has tried to find a balance between opposite constraints.